More than the bottom line - KEUNG, Edmund (Institutional Knowledge at Singapore Management University, 2019)
In the second instalment of a three-part series on financial literacy, SMU Dean of Postgraduate Professional Programmes and Associate Professor of Accounting (Practice) Themin Suwardy, NUS Associate Professor of Accounting Edmund Keung and SIT Associate Provost and Professor of Accounting Ho Yew Kee discussed three important accounting concepts that investors need to understand in order to know how a company is performing financially.